2020
DOI: 10.1016/j.ccell.2019.12.014
|View full text |Cite
|
Sign up to set email alerts
|

THEMIS-SHP1 Recruitment by 4-1BB Tunes LCK-Mediated Priming of Chimeric Antigen Receptor-Redirected T Cells

Abstract: Highlights d LCK promotes basal CAR-CD3z phosphorylation in the synapse of CAR.CD28z d THEMIS-SHP1 counteracts the effect of LCK in the synapse of CAR.4-1BBz d Engineering LCK kinase tunes up the antitumor activity of CAR.4-1BBz-T cells d Engineering druggable SHP1 phosphatase tunes down the function of CAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 42 publications
(48 reference statements)
2
100
0
Order By: Relevance
“…The distal PYAP subdomain initiates signaling by binding LCK (20,21), which has been confirmed in CARs (11,22).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The distal PYAP subdomain initiates signaling by binding LCK (20,21), which has been confirmed in CARs (11,22).…”
Section: Introductionmentioning
confidence: 81%
“…Similarly, LCK-mediated signaling is critical for CAR T cells with a CD8 transmembrane domain (11), and recruitment of LCK to the CAR synapse can enhance tumor killing in 4-1BB CARs (22). Ultimately, these mutations will be best evaluated in patients to determine how they impact clinical outcomes.…”
Section: Mut06 Has Reduced Exhaustion-related Gene Expression and Accmentioning
confidence: 99%
“…In a humanized mouse model, they demonstrated that this design effectively suppressed tumor growth without significant weight loss of the mice. The reduced cytokine release in the plasma after AP21967 administration indicated that toxicities such as CRS could be ameliorated by this strategy (55). Therefore, the cytotoxicity of CAR-T cells can be precisely controlled by small molecules to prevent possible severe side effects.…”
Section: Modifying Downstream Signaling Of Cd28ζ Carmentioning
confidence: 99%
“…Only very recently have the molecular mechanisms underpinning these functional differences begun to be systematically dissected. By comparing signaling downstream of CD28 and 4-1BB tail sequences in the context of otherwise identical CD19 CARs, one study [ 176 ] found that enhanced Lck recruitment amplifies both basal and antigen-induced phosphorylation in the CD28-containing CAR, while the unique ability to recruit phosphatase SHP1 (in a THEMIS-SHP1 complex) suppresses basal phosphorylation and attenuates antigen-induced phosphorylation in the 4-1BB-containing CAR. Importantly, the authors went on to show that engineering SHP1 recruitment into the CD28-containing CAR could ameliorate cytokine toxicity without sacrificing overall efficacy, emphasizing the utility of gaining detailed mechanistic understanding for engineering better therapies.…”
Section: Functional Consequences Of Car Design and Structurementioning
confidence: 99%